Long non‐coding RNA lnc‐DC in dendritic cells regulates trophoblast invasion via p‐STAT3‐mediated TIMP/MMP expression. (11th April 2020) - Zhang, Wen; Yang, Mengyuan; Yu, Ling; Hu, Yun; Deng, Yali; Liu, Yang; Xiao, Songyuan; Ding, Yiling
Abstract: Problem: Dendritic cells are the primary antigen‐presenting cells that contact trophoblasts at the beginning of pregnancy. Excessive DCs maturity is described in some pregnancy complications, such as pre‐eclampsia and fetal growth restriction, which are characterized by impaired trophoblast invasion. However, the mechanism is unclear. The long non‐coding RNA long non‐coding RNA DC (lnc‐DC) is expressed exclusively in conventional human DCs and induces DC differentiation and maturation by promoting signal transducer and activator of transcription 3 (STAT3) phosphorylation. Our previous investigation proved lnc‐DC and p‐STAT3 are elevated in pre‐eclampsia. This research is to study the mechanism of lnc‐DC and trophoblast invasion. Method of study: We transfected DCs with lnc‐DC shRNA or a lentivirus for lnc‐DC overexpression and cocultured these treated DCs with trophoblast under different conditions. Transwell assay and wound healing assay were used to detect the trophoblast invasion ability. We also tested the matured DCs and Th1 cells as well as the p‐STAT3. Results: We found that lnc‐DC promoted DC maturation and inhibited trophoblast invasion without the involvement of CD4 + T cells. And the p‐STAT3 agonist could reverse the lnc‐DC function. Conclusion: Mature DCs may be involved in altering trophoblast invasion through the overexpression of lnc‐DC, which increases p‐STAT3 levels and the tissue inhibitor of metalloproteinase‐1 (TIMP‐1)/matrix metalloproteinase‐9 (MMP‐9) and tissue inhibitor of metalloproteinase‐2 (TIMP‐2)/matrix metalloproteinase‐2 (MMP‐2) ratios. Thus, lnc‐DC is a promising novel target for regulating trophoblast invasion. Abstract : Inhibition or overexpression of lnc‐DC altered DC maturation and thus regulated trophoblast invasion.